Chief Minister’s Jan Awas Yojna-2015 – An Emerging Prospect Of Affordable Housing In Rajasthan - DWIVEDI, HARSH; AGRAWAL, GIRI RAJ (The journal of contemporary issues in business and government, 2021)
After independence, the country’s urban population has exploded. The migration of people from rural and semi-urban areas to urban areas is a common occurrence. They face a significant shelter challenge in urban areas, which is out of reach due to scarce resources, expensive property, construction materials, and labour, as well as a general lack of infrastructure in urban areas. As a result, policymakers must take a constructive position in encouraging the development of EWS and LIG housing stock in urban areas. According to TG-12 reports, the poorer parts of India accounted for 96 percent of the housing shortage.3 As a result policy proposals were needed to close the gap between urban housing demand and supply. The Pradhan Mantri Awas Yojna-2015 (Urban) and the Chief Minister’s Jan Awas Yojna-2015 (Rajasthan) will serve as a watershed moment in this regard. Central and state governments strategically manage the cost of affordable housing units for the EWS and LIG segments by subsidizing affordable houses and extending various incentives, exemptions, rebates, relaxations, interest subsidy, and facilities to various stakeholders with the aim of maximising the use of valuable urban lands to provide EWS and LIG houses at affordable rates to targeted groups. This research paper aims to evaluate the integration of both schemes in order to meet affordable housing goals in the state of Rajasthan, as well as summarise the perspectives of various stakeholders on both schemes.